HOUSEHOLD SOCIOECONOMIC FACTORS AFFECTING FAMILY FOOD CONSUMPTION: A CASE STUDY OF HOUSEHOLDS IN GUNUNG JATI VILLAGE EAST JAVA PROVINCE INDONESIA - Maula, Lia Rohmatul; Susilowati, Dwi (University of Islam Malang, 2024)
Food adequacy is often a measure of household welfare. Household food consumption is the need of household members for food which aims to strengthen food security at the household level. The quality and quantity of food consumed by each individual will influence the individual's nutritional status. This research aims to analyze how socioeconomic factors influence family food consumption. The research was conducted in Gunung Jati Village, Jabung District, Malang Regency using probability sampling techniques in the form of random sampling. The sample was selected by accidental sampling as many as 49 mothers with toddlers. The data analysis method used is logistic regression. Socioeconomic factors that have the potential to influence mothers' decisions in fulfilling family food consumption are the mother's education (X2), household income (X3), and mother's nutritional knowledge (X4).